A educação em saúde na prática cotidiana: atuação dos cirurgiões-dentistas do PSF de Natal-RN - Fernandes, Maria Julieta Medeiros (2007)
Considering education a support to health promotion, care integration and citizenship formation,the purpose of this research was to analyze the perception of the oral surgeons from the Family Health Program of Natal-RN over education in health as well as their performance as educators based on their activities on the program. A qualitative study was accomplished by a semi-structured interview and a Free Association of Words Test with 80 oral surgeons from the Family Health Program of Natal-RN. The instruments were analyzed through the meaning analysis and the Central Nucleus of Vergès Theory. The results showed a lack of planning in health actions so there is no standardization on the educative practices done by the oral surgeons which mostly are focused on scholars. There was an agreement among the group according to the oral surgeons´ perception about education in health that education is related to its function of recall prevention ideas to the population. Most part of the context units analyzed by the professionals´ speech show the knowledge of education in health as an inadequate behavior change instrument of the individuals. An interesting point was a quotation cited by some professionals that included actual themes such as citizenship, motivation and life quality, put inside the speech of education in health. To the oral surgeons the biggest difficulties on the development of the educative actions are due to the lack of incentive by the Municipal Health Bureau and to the detachment and lack of valorization of the themes by the population. The oral surgeons consider themselves co-responsible for the formation of a population which is able to request its health. They also mention the knowledge about the need of the community participation on the planning of the Family Health Program actions. Finally, it is notable the need for more encouragement so the oral surgeons can be more capable and have more interest in applying education in health on the perspective of a new model in health, because once capable and stimulated they can awake the population to education importance as a great transformation instrument for people searching for a fair, equalitarian and citizeness society